Multicultural-Based Social Interactions: The Case of a Private High School - Putra, Zeri Milyuta; Fatmariza, Fatmariza (Indonesian Research Journal in Education |IRJE|, 2024)
This research analyzed multicultural-based social interactions at a private High School on cultural and religious backgrounds and aimed to understand the patterns of social interaction in a multicultural educational environment. It was a mixed method study, where the informant selection technique was carried out by using a purposive sampling method, while data were collected through interviews, observation, and document analysis. The research results highlighted on the success of multicultural education in creating an inclusive environment. The implications of these findings support the development of broader educational programs to increase positive social interactions in multicultural schools. This research contributes to a practical understanding of multicultural education strategies that can be applied in Indonesian education.